The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1080/13607863.2021.1947968
|View full text |Cite
|
Sign up to set email alerts
|

Pain in nursing home residents with dementia and its association to quality of life

Abstract: Word Count: ca 4400 words (numbered references, APA reference style increases the word count)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 67 publications
2
26
0
1
Order By: Relevance
“…9 Pain is a common symptom among people with dementia living in nursing homes. [10][11][12][13] In a recent study, van Dam et al found that…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…9 Pain is a common symptom among people with dementia living in nursing homes. [10][11][12][13] In a recent study, van Dam et al found that…”
Section: Introductionmentioning
confidence: 99%
“… 10 Helvik et al state that 35.5% of their participants had clinically relevant pain on admittance to a nursing home. 11 A review conducted by Corbett et al indicates that 50% of people with dementia regularly experience pain and that the prevalence of pain in nursing home patients might be higher. 12 Pain in this patient group is often related to musculoskeletal, gastrointestinal and cardiac conditions, genitourinary infections, and wounds.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pain is not only an unpleasant experience but also found to be quite prevalent in NH residents with dementia. A prevalence up to 80% has been reported in these NH residents but it is reported to vary considerably [10][11][12][13][14][15][16][17][18][19][20], which may be due to differences in participant characteristics, pain treatment, definition of pain, and methodology used in the studies [15].…”
Section: Introductionmentioning
confidence: 99%